2019
DOI: 10.3233/ch-180422
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of red blood cell characteristics on diabetic retinopathy development and progression in type 2 diabetes mellitus

Abstract: BACKGROUNDAlthough it is considered that the pathogenesis of diabetic retinopathy (DR) in type 2 diabetes mellitus (T2DM) is primarily due to chronic hyperglycemia resulting in vascular changes and retinal ischemia, the red blood cells (RBCs) disorders might also represent an important pathophysiological risk factor.OBJECTIVETo evaluate whether the RBC properties contribute to DR development and progression in T2DM.METHODSThis prospective observational study comprised 247 persons with T2DM free of DR or with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
3
12
0
1
Order By: Relevance
“…Our findings are in agreement with Khan et al's study which found that greater BMI is significantly associated with foot ulcer while high BP or T2D is insignificantly linked to FUs [18]. Significantly high red cell distribution width value in DFUs is in agreement with other studies that demonstrated that high RDW is a marker of complicated T2D [8, 19]. A low value of PDW and high ESR level are significant discriminators between noninfected DFUs and non-DFU patients while MPV values in both groups II and III do not show a significant difference.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in agreement with Khan et al's study which found that greater BMI is significantly associated with foot ulcer while high BP or T2D is insignificantly linked to FUs [18]. Significantly high red cell distribution width value in DFUs is in agreement with other studies that demonstrated that high RDW is a marker of complicated T2D [8, 19]. A low value of PDW and high ESR level are significant discriminators between noninfected DFUs and non-DFU patients while MPV values in both groups II and III do not show a significant difference.…”
Section: Discussionsupporting
confidence: 93%
“…Other authors suggested that MPV, which increases in T2D, is a risk factor for peripheral artery disease that is associated with T2D [7]. Red distribution width (RDW) percentage was significantly increased in complicated diabetic patients and directly correlated with glycated hemoglobin (HbA1c) [8]. There is an inverse relationship between the level of nitric oxide (NO) with the MPV and RDW, as low levels of nitrites were associated with aggregation of red cells and platelets, which may be prone to the development of peripheral artery disease [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…By observing changes in the morphology and structure of erythrocytes in diabetics, a better understanding of the progression of diabetes can be achieved [20]. [22]. MCV is also reported to be a potential risk factor of peripheral artery disease and is related to disease severity; therefore, it can be used as a predictor of diabetic macrovascular complications [23].…”
Section: Erythrocyte Changes Inmentioning
confidence: 99%
“…HbA1c has an enhanced affinity toward O 2 ; therefore, higher HbA1c concentrations lead to difficulties in releasing oxygen to cells and reduced oxygentransporting function of erythrocytes [43]. Blaslov [22] reported a positive correlation between HbA1c and diabetic retinopathy (DR), which was caused by the reduced affinity of erythrocytes to oxygen. Local hypoxia also results in the thickening of glomerular basement membrane and thus induces DN.…”
Section: Fluiditymentioning
confidence: 99%
“…Although several studies have investigated the relationship between RDW and DR, the results have been controversial now. Blaslov et al reported that high RDW might be a risk factor for the pathogenesis and progression of DR, while Malandrino et al found no association between RDW and DR [ 17 , 18 ]. In this study, we reviewed the clinical and laboratory data of inpatients with DR over the past five years to investigate whether high RDW was associated with DR.…”
Section: Introductionmentioning
confidence: 99%